APPLICATION OF COMBINED ANALYSIS WITH BIPLOT METHOD FOR EXPLAINING AGRONOMIC TRAITS OF THE UPLAND RICE FROM MINORITY FARMERS IN PRACHUAP KHIRI KHAN, THAILAND - P. Na Chiangmai; J. Meesumlee; S. Brooks (Journal of Animal and Plant Sciences, 2022)
Genetic studies in upland rice in Thailand, both inside and outside the farming area, can provide the fundamental knowledge for management of the upland rice under the ongoing changes and pressing issues, such as low yield, land use policy in upland areas, and the impact of social issues. The present study exploys the combined analysis with biplot methods (modeling of main effect of genotype and the genotype-by-environment interaction; GGE) to obtain information on the response of upland rice genetics and characteristics under changing planting environments. In this study, seven native upland rice varieties were received from hill tribe farmers in Prachuap Khiri Khan Province, Thailand. These rice varieties were subsequently replanted in plots located in three different sites, in two different provinces for three consecutive years in the rainy season. The results indicate that three traits viz, seed number panicle-1 (SNP), percent of seed filling (PSF), and plant height (PH) varied significantly under genetic x environment (GxE) analysis. For seed yield per hill (SYH) in polygon form, three varieties (Aung Jerng Yai, Khao Niaw Pala-U and Beu Ge) were higher most adaptive genotypes in each environment (Environments 1, 2, and 3, respectively). Among these three varieties, Khao Niaw Pala-U exhibited the best mean and stability for yielding as determined by biplot method.
Keywords: Oryza sativa (L.); indigenous varieties; upland rice; combine analysis; GxE interaction